Practice Advisory for the Prevention, Diagnosis, and Management of Infectious Complications Associated With Neuraxial Techniques: An Updated Report by the American Society of Anesthesiologists Task Force on Infectious Complications Associated with Neuraxial Techniques and the American Society of Regional Anesthesia and Pain Medicine. Issue 1 (March 2018) - Unknown
Abstract : ( Anesthesiology . 2017;126(4):585–601) The article is an update to the "Practice Advisory for the Prevention, Diagnosis, and Management of Infectious Complications Associated with Neuraxial Techniques by the ASA Task Force on Infectious Complications Associated with Neuraxial Techniques" published in 2010. This update from the American Society of Anesthesiologists includes the most recent scientific literature. It is intended to support clinical decision making, but does not have the same support from the technical literature as standards or guidelines.